"HIV Is a Gift": Posttraumatic Growth in Women With HIV. (April 2022) - Lennon-Dearing, Robin
Given the universally high rates of trauma in women living with HIV and the positive health benefits associated with posttraumatic growth, recognizing how posttraumatic growth is expressed in words by women with HIV has important application to clinicians working with this population. This study examined qualitative narratives from a women's HIV support group to look for spontaneous statements and comments that corresponded to the five domains of posttraumatic growth identified by Tedeschi and Calhoun. Participants in this study described how their lives had been transformed, consistent with posttraumatic growth, into what was described as a "gift." Implications for clinical practice are offered.